Polyoxometalates-mediated facile synthesis of Pt nanoparticles anchored on an ordered mesoporous carbon for electrochemical applications. Issue 96 (29th September 2016) - Li, Bingqian; Zhang, Tongrui; Wang, Huan; Zhao, Xiaoqing; Li, Fang; Liu, Mengjun; Zhao, Jincan; Zhang, Yufan
Abstract : A green and facile strategy to develop electrochemical sensors through the rational design of platinum nanoparticles@polyoxometalate decorating ordered mesoporous carbon (Pt@POMs-OMC) nanohybrids. Abstract : This study demonstrates a green and facile strategy to develop electrochemical sensors through the rational design of platinum nanoparticles@polyoxometalate decorating ordered mesoporous carbon (Pt@POMs-OMC) nanohybrids. The Keggin-type POMs, H3 PW12 O40, was applied to serve as a both reducing and stabilizing agent. The as-prepared nanohybrids were characterized comprehensively by X-ray diffraction, X-ray photo-electron spectroscopy, energy-dispersive X-ray spectroscopy, and transmission electron microscopy. The novel nanohybrids of Pt@POMs-OMC can provide new features for electro-catalytic applications because of the synergetic effects of Pt nanoparticles and OMC materials. This study reports on the use of Pt@POMs-OMC as an effective sensing template for enhanced hydrazine, hydrogen peroxide (H2 O2 ), and nitrobenzene (NB) electrochemical detection for the first time. It exhibits a steady amperometric response towards hydrazine in the linear concentration range of 10–840 μM with a sensitivity of 2.92 μA mM −1 and from 840 to 1400 μM with a sensitivity of 7.32 μA mM −1 ; the limit of detection was calculated to be 3.41 μM. It shows a steady amperometric response towards H2 O2 in the linear concentration range of 5–5400 μM with a sensitivity of 10.64 μA mM −1 and a limit of detection of 1.09 μM. The NB sensor displays a linear range of 3.98–672.55 μM with a sensitivity of 102.62 μA mM −1 and a limit of detection of 3.82 μM. The successful fabrication of Pt@POMs-OMC holds great promise for the design of electrochemical sensors and is a promising material to promote the development of new electrode materials.